2017
DOI: 10.1308/rcsann.2016.0270
|View full text |Cite
|
Sign up to set email alerts
|

Patterns, timing and consequences of post-thyroidectomy haemorrhage

Abstract: INTRODUCTION Post-thyroidectomy bleeding is a low frequency but potentially life threatening event that is very difficult to predict. Given the increasing drive towards thyroidectomy with same day discharge, this study was conducted with the aim of identifying patterns, timing and consequences of post-thyroidectomy bleeding to assess the feasibility of day-case thyroidectomy. METHODS All patients who underwent a thyroidectomy between 2008 and 2015 at our institution were identified. Patterns, timing and conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 23 publications
4
35
1
Order By: Relevance
“…The reoperation rate for bleeding in our unit was 1.3%. This falls within the range reported in the literature (0.07 to 4.2%) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Generally, lower rates of reoperation for bleeding have been reported in patients undergoing parathyroid surgery alone (0 to 1.1%) [2,11,16,18,19] or when rates in parathyroid surgery and thyroid surgery are pooled (0.4 to 0.8%) [2,11,16,19].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The reoperation rate for bleeding in our unit was 1.3%. This falls within the range reported in the literature (0.07 to 4.2%) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Generally, lower rates of reoperation for bleeding have been reported in patients undergoing parathyroid surgery alone (0 to 1.1%) [2,11,16,18,19] or when rates in parathyroid surgery and thyroid surgery are pooled (0.4 to 0.8%) [2,11,16,19].…”
Section: Discussionsupporting
confidence: 83%
“…The occurrence of significant bleeding 6 h after surgery is cited as a concern in the routine adoption of day case thyroid surgery [28]. Given most bleeds occur within 24 h after surgery, some have argued for at least 24 h of observation [13]. Others have argued that day case thyroid surgery is feasible with appropriate patient selection, patient support system, and experienced surgical teams [19].…”
Section: Management Of Bleeding After Thyroid And/ or Parathyroid Surmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, two patients with PH had dyspnea, and oxygen saturation in blood continued to decline; after emergency tracheotomy at the bedside, and timely hemostasis in the operating room, their lives were saved. OS at 5 years for the three groups was 90.70%, slightly lower than that reported by Liu et al 13 and Farooq et al 14,15 This difference may have been due to the late stage of enrolment, older age and other systemic diseases.…”
Section: Discussioncontrasting
confidence: 61%
“…The finding of bleeding occurring within 24 hours is consistent with results from other studies, which showed that all significant hemorrhage associated with thyroid surgery usually occurs within 24 hours of surgery. [17][18][19] Twenty-four hours is the standard observation time for short stay thyroidectomy. Present study, combined with evidence from other studies, showed that the short stay model does not pose any additional safety risks to patients in terms of hemorrhage.…”
Section: Discussionmentioning
confidence: 99%